Respuesta :

Azieq
3x - 2 ( 5x + 4 ) - 1 = 0
3x - 10x - 8 - 1 = 0
7x = - 9
x = - 9/7

y = 5 ( - 9/7 ) + 4
y = - 45/7 + 4
y = - 3/45/7

Answer:

[tex]x=\frac{-9}{7}[/tex]

[tex]y=\frac{-17}{7}[/tex]

Step-by-step explanation:

We have been given the equation:

[tex]3x-2y-1=0[/tex]

And [tex]y=5x+4[/tex]

Second equation can be rewritten as:

[tex]5x-y=-4[/tex]

We will solve the equations:

[tex]3x-2y=1[/tex]      (1)

[tex]5x-y=-4[/tex]       (2)

Multiply equation (1) by 5 and equation (2) by 3 we get:

[tex]15x-10y=5[/tex]      (3)

[tex]15x-3y=-12[/tex]       (4)

Now, subtract (4) from (3) we get:

[tex]-7y=17[/tex]

[tex]y=\frac{-17}{7}[/tex]

Now substitute [tex]y=\frac{-17}{7}[/tex] in equation (1) we get:

[tex]3x-2{\frac{-17}{7}}=1[/tex]

[tex]3x+\frac{34}{7}=1[/tex]

[tex]21x=-27[/tex]

[tex]x=\frac[-27}{21}[/tex]

[tex]x=\frac{-9}{7}[/tex]